Efektivitas Metode Drill terhadap Hasil dan Motivasi Belajar Bahasa Arab Siswa Sekolah Dasar: Penelitian Tindakan Kelas pada Materi Fi’il Madhi Shohih Salim - Tomo, Yarkoni Budi; Putra, Sudarmadi (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to improve students’ learning outcomes and motivation in Arabic language learning, particularly in the topic of fi’il madhi shohih salim, through the implementation of the drill method in Class V-C of SDIT Al-Mannan Boyolali. The background of this research lies in the low level of student engagement and achievement caused by monotonous and less contextual teaching methods.Method – The study employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, consisting of four stages: planning, action, observation, and reflection. The research subjects were 35 female students of Class V-C in the 2024/2025 academic year. Data were collected through tests (pre-test, cycle I, and cycle II), observation of learning activities, interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman. Findings – The students’ average score increased from 60.1 in the pre-action stage to 74.0 in cycle I and 82.3 in cycle II, with learning mastery improving from 45% to 85%. Observation results indicated an increase in students’ participation, confidence, and courage in speaking and writing Arabic. Classroom learning activities became more dynamic, characterized by enhanced group interaction and greater student involvement in repetitive exercises. Overall, the application of varied drill techniques through language games and visual media effectively strengthened students’ morphological memory while maintaining their learning motivation. Research Implications – The findings imply that the drill method, when applied with variation and supported by engaging media, can serve as an effective strategy to enhance both learning achievement and motivation in Arabic language instruction. Teachers are encouraged to integrate the drill method with communicative and digital approaches to sustain student engagement and optimize long-term learning outcomes in similar educational settings.